2013
DOI: 10.2147/dddt.s53011
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of whole brain radiotherapy with or without erlotinib in patients with multiple brain metastases from lung adenocarcinoma

Abstract: The aim of this paper is to explore the efficacy of whole brain radiotherapy (WBRT) versus WBRT concurrent with erlotinib in patients with multiple brain metastases of lung adenocarcinoma. WBRT was administered at 30Gy/10f in both arms. In the combination arm, 150 mg erlotinib was given each day, starting the first day of radiotherapy and continuing for 1 month following the end of radiotherapy. Thereafter, pemetrexed or docetaxel monotherapy or the best supportive therapy was given to both arms. The intracran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 23 publications
2
95
1
2
Order By: Relevance
“…73,74 A phase II study from China has reported that the combination of WBRT and erlotinib has tolerable toxicities, and suggested a prolonged PFS and OS (class IIb). 75 Conversely, phase II (class IIa and b) 76,77 and phase III (class I) 78 trials in patients with NSCLC brain metastases not enriched for EGFR mutations failed to demonstrate a superiority of the combination of erlotinib with either SRS or WBRT over radiotherapy alone, with a suggestion of worse outcome in patients receiving the combined therapy. A Chinese phase II trial of WBRT with concurrent icotinib, another EGFR inhibitor, has suggested that the combination could improve survival compared with historical controls.…”
Section: Brain Metastases From Nsclcmentioning
confidence: 99%
“…73,74 A phase II study from China has reported that the combination of WBRT and erlotinib has tolerable toxicities, and suggested a prolonged PFS and OS (class IIb). 75 Conversely, phase II (class IIa and b) 76,77 and phase III (class I) 78 trials in patients with NSCLC brain metastases not enriched for EGFR mutations failed to demonstrate a superiority of the combination of erlotinib with either SRS or WBRT over radiotherapy alone, with a suggestion of worse outcome in patients receiving the combined therapy. A Chinese phase II trial of WBRT with concurrent icotinib, another EGFR inhibitor, has suggested that the combination could improve survival compared with historical controls.…”
Section: Brain Metastases From Nsclcmentioning
confidence: 99%
“…In an effort to increase drug concentrations in the brain, several studies have assessed high-dose regimens of gefitinib or erlotinib in patients with EGFR mutation-positive NSCLC and brain metastases [67,69]. A number of retrospective studies have assessed the combination of first-generation EGFR TKIs with whole-brain radiation therapy (WBRT), which is thought to increase permeability of the bloodbrain barrier [72][73][74]. These studies indicate that concomitant WBRT may enhance the intracranial activity of first-generation TKIs.…”
Section: Factors Influencing First-line Treatment Choice: Brain Metasmentioning
confidence: 99%
“…Nevertheless radiotherapy did not improve disease response and no significant differences in ORR were documented. In general, cranial irradiation caused a rate of neurological adverse events higher than that reported in studies with TKIs alone (84)(85)(86), but lower than that of the concurrent upfront WBRT/TKIs studies (92,93). By limiting the analysis to prospective studies, there was no significant difference in intracranial disease control and survival outcomes between concurrent upfront WBRT plus TKIs and TKIs alone.…”
Section: Standard Schedulesmentioning
confidence: 81%
“…Concomitant therapy was also compared both to EGFR-TKI alone and WBRT alone (90,92,97,98,123). Ceresoli et al (90), in a previously mentioned study, evaluated 41 NSCLC pts with BM.…”
Section: Radiotherapy and Egfr-tkismentioning
confidence: 99%